Induction of labor with prostaglandin E2 Oral - Casquero Bao, José (2015)
Induction of labor with oral prostaglandin E2 (PGE2) in 110 patients, succeeded in 100 vaginal births; there were 9 failures of induction and cesarean section, with an effectiveness rate of 90.9%. Analysis of the results of the 100 pregnant women with vaginal delivery is: 53 were elective and 47 indicated; by post maturity (18 patients), dysfunctional labor (13), premature rupture of membranes (9), toxemia (5), diabetes (2). EI 86% had birth with one induction session without difference between elective and in you dicadas. PGE 2 was administered in doses of progressive time from 0.5 to 2 mg. The patients had clinical monitoring practice noting incidents related to stimulation, labor, delivery and newborns. Pelvic Bishop score was taken as a prognostic indicator of successful induction. 24.5% of elective inductions and 47% of the indicated higher scores were 7, considered very favorable. This indicator keeps indirectly related to the total dose of PGE 2 necessary to achieve vaginal delivery and transverse induction time; but not related to age, weight index of the mother or elective induction condition. In the 95 infants showed no hypoxia (Apgar 8 or more) but 4 had moderate hypoxia (Apgar 4-7), and one severe hypoxia (Apgar 1); this was related to the uterine contraction disorders secondary to PGE2 administration. Maternal side effects, fever, nausea and diarrhea were mild.